Encapsulation of avocado oil in amylose solution from cassava starch - Pérez-Monterroza, Ezequiel José [UNESP]; Chaux-Gutiérrez, Ana María [UNESP]; Nicoletti, Vânia Regina [UNESP] (Hindawi, 2018)
Encapsulation of avocado oil was carried out mixing it with amylose extracted from cassava starch. Then, the oleogel formed was retrograded at 8 and −18 °C for 24 hr and later dried by freeze-drying or vacuum at 3.3 kPa at 60 °C. Samples were characterized by X-ray diffractometry, FT-IR spectrometry and differential scanning calorimetry (DSC). The lutein and neoxanthin content was also determined. Results obtained from DSC and FT-IR spectroscopy indicated no formation of inclusion complexes V-type of amylose. Nevertheless, the results from X-ray diffractometry showed that samples had a diffraction pattern characteristics from V-type amylose complex. The samples that retrograded at −18 °C and dried using freeze-drying had a slight higher encapsulation degree than the samples retrograded at 8 °C. Practical applications: Xerogels and cryogels from amylose of cassava can be considered an interesting tool for encapsulation of edible oil rich in bioactive compounds such as lutein and neoxanthin. Xerogels and cryogels are a potential biodegradable matrix for loading biocompounds, as well as an alternative for formulating controlled delivery systems of nutrients.